2005
DOI: 10.1002/app.22461
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐curable unsaturated polyester inorganic/organic hybrid films

Abstract: An unsaturated polyester, based on maleic anhydride, 1,6-hexanediol, and trimethylol propane, was formulated with tetraethylorthosilicate (TEOS) oligomers and a coupling agent to prepare inorganic/organic hybrid films. TEOS oligomers were prepared through the hydrolysis and condensation of TEOS with water, and 3-(triethoxysilyl)propylisocyanate was used as the coupling agent between the organic and inorganic phases. The hybrid materials were cured by moisture via sol-gel chemistry and by the UV curing of unsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Inorganic silicate oligomers may function as a reactive diluent and not only help to reduce viscosity of the resin but also may increase the mechanical properties of the films. 38 UV-moisture dual-curable inorganic-organic hybrid coatings based on UPE binders and silicate-clusters were successfully prepared. In situ formed nano-to microsize inorganic clusters increased the abrasion resistance, adhesion, tensile strength and fracture toughness of the films.…”
Section: Uv-moisture Dual-curable Coatingsmentioning
confidence: 99%
“…Inorganic silicate oligomers may function as a reactive diluent and not only help to reduce viscosity of the resin but also may increase the mechanical properties of the films. 38 UV-moisture dual-curable inorganic-organic hybrid coatings based on UPE binders and silicate-clusters were successfully prepared. In situ formed nano-to microsize inorganic clusters increased the abrasion resistance, adhesion, tensile strength and fracture toughness of the films.…”
Section: Uv-moisture Dual-curable Coatingsmentioning
confidence: 99%
“…Numerous organic–inorganic hybrids based on linear polymers and thermosetting polymers have been examined in literature. However, only a few studies have been reported on hybrids based on polyesters, either linear, unsaturated or hyperbranched polyesters . Ester groups in polyester chains are not strong enough to form hydrogen bonds with silanols, so the use of a type of polyester which contains hydroxyl groups is of a great interest to increase the interfacial forces between the polymer and the silica network.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, these hybrid sol‐gel photomaterials were mainly synthesized from radically reactive organotrialkoxysilanes through a two‐step process: a preliminary sol‐gel step in solution was followed by the photopolymerization of the resulting functional polysilsesquioxane, thus affording a type‐II polysiloxane/poly(meth)acrylate hybrid film 10–15. An alternative route was developed by Soucek and coworkers: oligomers based on TEOS or reactive organoalkoxysilane were formed in a preliminary sol‐gel step before being mixed with radically reactive resins to be subsequently photopolymerized 16–18. Acrylate silane precursors were also employed as grafting or coupling agents in a view to enhance the nanoparticles or metal alkoxides dispersion in a radically photocurable organic host matrix 19–26.…”
Section: Introductionmentioning
confidence: 99%